Adobe After Effects : a complete course and compendium of features - Goldsmith, Ben (Rocky Nook, 2022)
Adobe After Effects: A Complete Course and Compendium of Features is your guide to editing and enhancing videos in Adobe After Effects. Whether you’re animating text or objects, changing a scene’s setting, or creating a 3D scene, After Effects is the tool for you—and this book will teach you what you need to know. First, with a complete Course that includes a set of projects and lessons derived from video editor and Adobe Certified Instructor Ben Goldsmith, you will learn the procedures needed to use After Effects effectively and professionally. Dozens of exercises are included that can be applied to any videos you have in mind. Through step-by-step lessons, you’ll be exposed to all of After Effects’ features in practical contexts and its best practices for optimal workflows. To complete the Course, we’ll supply lesson documents and their assets to download, so you can work alongside the text. Then, for greater depth of knowledge and subsequent reference, you’ll use the Compendium to uncover more of the “how” and “why” of After Effects. With each topic easy to access, you can find and explore all of Premiere Pro’s key features and concepts in depth. With cross-references between the Course and Compendium, the two parts of the book complement each other perfectly. Best of all, when the lessons in the Course are done, the Compendium will continue to serve for months and years to come.